(Re)criando (mini)contos de terror: uma experiência de ensino de leitura e escrita de gênero multimodal - Cabral, Adriana Rosa da Silva (2015)
Given the multiplicity of languages and media present in contemporary texts, the work with digital genres characterizes itself as essential for teaching, reading and writing. Virtual media is already present in many dayly activities that require the use of language. This shows that the globalized world brings new demands of literacy and various reading practices. Given this perspective, we propose to work the multiliteracies present in the new texts from the enunciative discourse Bakhtinian assumptions. For this, we chose to be as the object of research / intervention, the horror flash fiction multimodal discursive genre, because it is a multissemiótico digital statement of virtual circulation. In this context, this study aimed to understand how the teaching of this kind can contribute to the development of knowledge related to reading and text production, required by multiliteracies, by performing a Didactic Sequence in the classroom, specifically for two classes of elementary school, 7th and 8th grades of public school. The research was based on Bakhtin's theory and the Circle (2009, 2011) on gender perspective in a dialogic and the proposed Dolz and Schneuwly (2004) for the text of teaching through sequences Teaching. We also use the precepts of multiliteracies focused on Rojo (2012, 2013). The methodology used was based on a qualitative approach. We consider the analysis of minicontos produced by students, it's own hibridism of multiliteracies, the discursive characteristics such as composition, style and subject content, in addition to relations dialogicity present in these statements. At the end of the study, we realized that our intervention contributed to the expansion of knowledge of the subjects involved related to reading and multimodal genre production.